Measurement challenges for childhood obesity research within and between Latin America and the United States. (4th May 2021) - Berrigan, David; Arteaga, S. Sonia; Colón‐Ramos, Uriyoán; Rosas, Lisa G.; Monge‐Rojas, Rafael; O'Connor, Teresia M.; Pérez‐Escamilla, Rafael; Roberts, Elizabeth F. S.; Sanchez, Brisa; Téllez‐Rojo, Martha Maria; Vorkoper, Susan; ,
Summary: Childhood obesity is a major public health challenge across Latin America and the United States. Addressing childhood obesity depends on valid, reliable, and culturally sensitive measurements. Such progress within and between countries of the Americas could be enhanced through better measurement across different age groups, different countries, and in sending and receiving communities. Additionally, better and more comparable measurements could accelerate cross‐border collaboration and learning. Here, we present (1) frameworks that influenced our perspectives on childhood obesity and measurement needs across the Americas; (2) a summary of resources and guidance available concerning measurement and adaptation of measures for childhood obesity research; and (3) three major areas that present challenges and opportunities for measurement advances related to childhood obesity, including parental behavior, acculturation, and the potential to incorporate ethnographic methods to identify critical factors related to economics and globalization. Progress to reduce childhood obesity across the Americas could be accelerated by further transnational collaboration aimed at improving measurement for better surveillance, intervention development and evaluation, implementation research, and evaluation of natural experiments. Additionally, there is a need to improve training related to measurement and for improving access to valid and reliable measures in Spanish and other languages common in the Americas.